Pengaruh Sistem Informasi Akuntansi (SIA) dan Budaya Organisasi Terhadap Kinerja Pegawai dengan Pengendalian Internal sebagai variabel moderasi: Studi pada Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Tengah - Andi Negarawan Kamanre Islami Akrab; Femilia Zahra (Jurnal Riset Akuntansi, 2026)
This study aims to examine and analyze the effect of Accounting Information Systems (AIS) and organizational culture on employee performance, as well as the role of internal control as a moderating variable. This research employed a causal-comparative quantitative approach using a census (saturated sampling) technique, involving a population of 60 employees at the Regional Development Planning Agency (BAPPEDA) of Central Sulawesi Province. Primary data were collected through questionnaires and analyzed using statistical approaches based on Average Variance Extracted (AVE), Composite Reliability, and Cronbach’s Alpha to assess the validity and reliability of the research instruments. The results indicate that both Accounting Information Systems and organizational culture have a positive and significant effect on employee performance. Furthermore, internal control was found to positively and significantly moderate the relationship between Accounting Information Systems and employee performance, as well as the relationship between organizational culture and employee performance. These findings reinforce the perspectives of the Resource-Based View (RBV), contingency theory, and stewardship theory, in which internal control capability functions as a formal safeguarding mechanism that mitigates fraud risks associated with AIS while transforming organizational values into tangible Standard Operating Procedures (SOPs) to optimize organizational operational performance.